1984
DOI: 10.1152/ajpendo.1984.247.4.e456
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation to a reduced islet cell mass in dogs

Abstract: The quantitative insulin response to glucose stimulus can be drastically reduced by subtotal pancreatectomy. An 80% pancreatectomy was performed preserving the pancreatic duct in seven dogs. The insulin output into the portal vein and cephalic vein insulin after intravenous glucose challenge were measured. Output was recorded in 25 controls, and before and 2 wk after subtotal pancreatectomy in the seven animals. Histologic sections of the original resection were compared with the remnant of pancreas taken at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…In a study specifically designed to examine the potential for ␤-cell regeneration, Lö hr et al (25) found a 19% gain in ␤-cell mass 6 weeks after a 60% pancreatectomy in 7-month-old pigs, while an 80% pancreatectomy elicited a 56% increase in ␤-cell mass. Interestingly, when adult dogs were subjected to a similar 80% pancreatectomy, no recovery of insulin secretion or ␤-cell mass was found in the pancreas remnant (26). The most obvious explanation for the discrepancies between these studies is that the capacity for new ␤-cell formation declines with aging.…”
Section: Discussionmentioning
confidence: 99%
“…In a study specifically designed to examine the potential for ␤-cell regeneration, Lö hr et al (25) found a 19% gain in ␤-cell mass 6 weeks after a 60% pancreatectomy in 7-month-old pigs, while an 80% pancreatectomy elicited a 56% increase in ␤-cell mass. Interestingly, when adult dogs were subjected to a similar 80% pancreatectomy, no recovery of insulin secretion or ␤-cell mass was found in the pancreas remnant (26). The most obvious explanation for the discrepancies between these studies is that the capacity for new ␤-cell formation declines with aging.…”
Section: Discussionmentioning
confidence: 99%
“…In humans after hemipancreatectomy and dogs after an approximately two-thirds pancreatectomy, both the fasting plasma glucose and the insulin concentrations (measured by conventional immunoassay) were normal, raising the question, "How does a decreased capacity for insulin secretion adapt to prevent the development of diabetes?" The possibilities were examined by Marincola et al (31) in a study of dogs that had either sham surgery or ϳ80% pancreatectomy. In these studies, pancreatic insulin output was measured directly by sampling from the portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Marincola et al (28) reported that hepatic clearance of insulin may decrease after an 80% pancreatectomy in dogs. Indeed, the values remained remarkably constant after pancreatectomy compared with baseline values.…”
Section: Glucosementioning
confidence: 89%